Diagnostic Accuracy of Artificial Intelligence (AI) to Detect Early Neoplasia in Barrett's Esophagus: A Non-comparative Systematic Review and Meta-Analysis - Tan, Jin Lin; Chinnaratha, Mohamed Asif; Woodman, Richard; Martin, Rory; Chen, Hsiang-Ting; Carneiro, Gustavo; Singh, Rajvinder (Frontiers in Medicine, 2022)
Background and Aims: Artificial Intelligence (AI) is rapidly evolving in gastrointestinal (GI) endoscopy. We undertook a systematic review and meta-analysis to assess the performance of AI at detecting early Barrett's neoplasia. Methods: We searched Medline, EMBASE and Cochrane Central Register of controlled trials database from inception to the 28th Jan 2022 to identify studies on the detection of early Barrett's neoplasia using AI. Study quality was assessed using Quality Assessment of Diagnostic Accuracy Studies – 2 (QUADAS-2). A random-effects model was used to calculate pooled sensitivity, specificity, and diagnostics odds ratio (DOR). Forest plots and a summary of the receiving operating characteristics (SROC) curves displayed the outcomes. Heterogeneity was determined by I2, Tau2 statistics and p-value. The funnel plots and Deek's test were used to assess publication bias. Results: Twelve studies comprising of 1361 patients (utilizing 532,328 images on which the various AI models were trained) were used. The SROC was 0.94 (95% CI: 0.92- 0.96). Pooled sensitivity, specificity and diagnostic odds ratio were 90.3% (95% CI: 87.1%-92.7%), 84.4% (95% CI: 80.2%-87.9%) and 48.1 (95% CI: 28.4-81.5) respectively. Subgroup analysis of AI models trained only on white light endoscopy was similar with pooled sensitivity and specificity of 91.2% (95% CI: 85.7%-94.7%) and 85.1% (95% CI: 81.6%-88.1%) respectively. Conclusions: AI is highly accurate at detecting early Barrett's neoplasia and validated for patients with at least high-grade dysplasia and above. Further well-designed prospective randomized controlled studies of all histopathological subtypes of early Barrett’s neoplasia are needed to confirm these findings further.